Literature Review: Kebutuhan Gizi Pada Lansia - Rachmat Faisal Syamsu; Inayah Al Fatiha; Andini Sangkal (SEHATI: Jurnal Kesehatan, 2025)
The aging process involves a decline in the body's physiological functions, making optimal nutritional intake crucial for maintaining the health and quality of life of the elderly. This literature review aims to synthesize recent evidence on the nutritional status, influencing factors, and intervention strategies for the elderly. The method used was a literature review of articles published between 2020-2025, sourced from databases like PubMed, NCBI, and Google Scholar. Fifteen articles were selected based on inclusion criteria. The findings highlight several key themes: the critical role of adequate protein intake (≥1.3 g/kg BW/day) and its distribution throughout the day to prevent sarcopenia and frailty; the effectiveness of holistic dietary patterns like the Mediterranean diet; the double burden of malnutrition and significant geographical disparities in nutritional status among Indonesian elderly; the strong influence of socio-economic and cultural determinants; and the success of community-based intervention models, such as peer educators and integrated nutrition counseling in primary health services. In conclusion, a comprehensive and integrated approach, encompassing adequate nutrient intake, culturally adapted dietary patterns, routine screening, and community-based empowerment, is essential to improve the nutritional status and support healthy aging for the elderly. Further research is needed to develop interventions tailored to the specific characteristics of the diverse elderly population in Indonesia.